Elixir formulations of methanolic extract concentrates of garcinia kola, kola acuminata and kola nitida seeds and their antimicrobial activity (2008)
The crude methanolic extracts of Garcinia Kola (Gutiferae), Kola acuminata and Kola nitida (Sterculiaceae) seed powders were screened against some bacterial isolates consisting of six different Genera namely: Streptococcus, Staphylococcus, Escherichia, Proteus, Klebsiella and Pseudomonas, most of which were isolated from the respiratory tract and the rest from other sources like wounds, vagina and urethra. The extracts were found to be active on all the Gram-positive bacteria and some of the Gram-negative bacteria including Pseudomonas aeruginosa. The extracts Were then formulated into stable Elixir formulations at a concentration of 15mg/ml and screened against the same bacterial isolates. They were found to be active against all the selected Gram-positive bacteria used in were also susceptible to the three elixir formulations.